»Ako bi tekla Savinja ali Voglajna blizu Gradca, bili bi že davno z deželnim denarjem regulirani.« - Čuček, Filip (Prispevki za novejšo zgodovino, 2024)
Due to snowmelt and heavy rainfalls, the “mountainous” river Savinja was prone to flooding. The first serious attempts at regulating it started in the early 19th century and more systematically in the second half of the century. After the first extensive regulation between Mozirje (Prihova) and Levec (1876–1893), the riverbed was straightened, and the flow accelerated. The river also became faster in its lower part, carrying sediments all the way to Celje. However, in Celje, the river Savinja was not regulated during the Austrian period.
Keywords: Celje; deželni zbor; floods; poplave; Provincial Assembly; regulacije; regulation; reka Savinja; Savinja; Savinja Valley; Savinjska dolina